Analisis Perbandingan Kebangkrutan dengan Metode Altman Z-Score, Springate, dan Zmijewski - Ukhti Apse Raviani; Yanuar Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research was conducted to find out how much potential the company's bankruptcy is during this pandemic. Bankruptcy prediction is done by using Altman Z-Score, Springate, and Zmijewski methods. The study used a different test, namely the Kruskal-Wallis H Test. The companies used in this study were the hotel, restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange. The research sample uses 16 hotel, restaurant, and tourism sub-sector companiesilisted on the Indonesia Stock Exchange for the 2016-2020 periods. Sample selection using a purposive sampling technique. From the hypothesis test conducted, the results show that there are differences between the Altman Z-Score, Springate, and Zmijewski prediction methods in predicting bankruptcy. In this study, the Zmijewski method is the most accurate prediction model with an accuracy rate of 98% with the results of 2 companies experiencing bankruptcy. Next is the Altman ZScore method with an accuracy rate of 61% with the results of 8 companies experiencing bankruptcy and the Springateimethod withianiaccuracyirate of 30% with the results of 11 companies experiencing bankruptcy.